2021
DOI: 10.1002/celc.202001488
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Complexing Additives on the Reversible Deposition/Dissolution of Magnesium in an Ionic Liquid

Abstract: Aiming at a fundamental understanding of the synergistic effects of different additives on the electrochemical Mg deposition/dissolution in an ionic liquid, we have systematically investigated these processes in a combined electrochemical and theoretical study, using 1-butyl-1-methylpyrrolidinium bis (trifluoromethylsulfonyl) imide (BMP-TFSI) as the solvent and a cyclic ether (18-crown-6) and magnesium borohydride as additives. Both crown ether and BH 4 À improve Mg deposition, its reversibility, and cycling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 83 publications
5
25
2
Order By: Relevance
“…Due to the low solubility of magnesium hydroxide, the outer layer of deposition will undergo dissolution periodically, which makes it unstable, producing unstable voltage fluctuation 56 . The low solubility Mg(OH) 2 can be related to its standard Gibbs free energy, ΔGfθ0.25em (−833.7 kJ mol −1 ) where it establishes a high energy barrier which makes it difficult to dissolve in aqueous solution and has become the big hurdle to irreversible Mg electrode in rechargeable MAFC development to date as the study on reversibility of Mg is scanty 36,149 . Currently, the work on electrocatalyst material improvement is centered on addressing the sluggish oxygen reduction reaction at cathode such as the porous perovskites 150 and others, 151 developing a novel electrocatalyst that function to oxidize Mg(OH) 2 layer is worthy to be paid attention to.…”
Section: Current Challenges and Approachesmentioning
confidence: 99%
“…Due to the low solubility of magnesium hydroxide, the outer layer of deposition will undergo dissolution periodically, which makes it unstable, producing unstable voltage fluctuation 56 . The low solubility Mg(OH) 2 can be related to its standard Gibbs free energy, ΔGfθ0.25em (−833.7 kJ mol −1 ) where it establishes a high energy barrier which makes it difficult to dissolve in aqueous solution and has become the big hurdle to irreversible Mg electrode in rechargeable MAFC development to date as the study on reversibility of Mg is scanty 36,149 . Currently, the work on electrocatalyst material improvement is centered on addressing the sluggish oxygen reduction reaction at cathode such as the porous perovskites 150 and others, 151 developing a novel electrocatalyst that function to oxidize Mg(OH) 2 layer is worthy to be paid attention to.…”
Section: Current Challenges and Approachesmentioning
confidence: 99%
“…This may create a severe obstacle in the RTIL environment due to the high concentration of counter ions. Indeed, reductive decomposition of the TFSI − anion in the presence of Mg had been identified in several studies and proposed as a major reason for the observed passivation of the electrode for reversible Mg deposition/stripping or O 2 reduction/evolution [10,11,15,25–27] . This was attributed to Mg 2+ complex formation, where TFSI anions are coordinated to Mg 2+ , [28,29] and decomposition of TFSI − upon reduction of the Mg 2+ central ion to Mg + .…”
Section: Introductionmentioning
confidence: 98%
“…Recently we started a systematic study on the deposition/stripping of Mg and the reduction/evolution of O 2 from/in a room temperature ionic liquid (RTIL), specifically in 1‐butyl‐1‐ methylpyrrolidinium bis(trifluoromethylsulfonyl) imide (BMP‐TFSI), [10–15] which will be continued in the present study. RTILs are attractive candidates as solvent in Li and post‐Li ion batteries because of their wide electrochemical stability window, low flammability and low vapor pressure, [16–18] where the latter is especially important for metal‐air batteries [19–24] .…”
Section: Introductionmentioning
confidence: 99%
“…Merely, a handful of studies reported the electrochemically induced passivation film formation at the Mg electrolyte/electrode interface and its microscopic nature. , Involvement of the adsorption–desorption processes and formation of the complexes at the interface during Mg deposition–dissolution are extremely complicated and difficult to be studied simply by cyclic voltammetry and ex situ analysis methods. , The lack of adequate in situ techniques is a major roadblock preventing us from understanding the interfacial processes in Mg electrolytes, which are crucial to the development of a practical rechargeable Mg system. Thus, it is critical to provide an in-depth analysis of the interfacial evolution at the Mg metal anode.…”
Section: Introductionmentioning
confidence: 99%